Effect of Berthing Time and Berth Output on Conventional Donation Utilization at PT Pelindo II Palembang Branch - Barasa, Larsen; Malau, April Gunawan; Sumali, Bambang (International Review of Management and Marketing, 2019)
Boombaru Port which is managed by PT Pelindo II Palembang Branch is a marine transportation infrastructure that plays an important role and function in the transportation wheel in the South Sumatra area. This is because this port is located in the city of Palembang as a center of government, trade and activitiestourism in South Sumatra. Based on data in 2017, the problem at this port is the high berthing time of ships at conventional docks, the realization of berth output is lower than the potential amount of cargo unloaded and loaded at conventional docks, and not achieving the target of conventional dock utilization. The purpose of this study is to find out and analyze how much influence berthing time, berth output together on the utilization of conventional docks. This research was conducted by collecting and processing data on ship and goods service performance and facilities and equipment utilization format reports in 2017. In this study it was found the average loading and unloading speed based on berthing time at conventional docks does not meet the loading discharge rate that has been determined based on the service level agreement. There is a difference in value between loading discharging rate with time and the loading discharging rate with working time . To optimize the utilization of conventional docks to match the predetermined RKA, streamlining the berthing time faster so that the output berth will also be optimized properly. To streamline berthing time and optimize berth output by accelerating loading and unloading activities at conventional docks by increasing the number of loading and unloading equipment at conventional docks such as jib cranes and head trucks. For the use of one jib crane / hour unit requires three head truck units. So for the addition of one jib crane unit also requires three head truck units. In order to support the loading and unloading activities at conventional docks and to avoid the high idle time at berthing time of the ship, care and maintenance of the loading and unloading equipment is needed so that the loading and unloading equipment can always be used. Keywords: Berthing Time, Berth Output, Berth Occupancy Ratio, Dock Utilization JEL Classifications: L62, R41, R42 DOI: https://doi.org/10.32479/irmm.8531